Heart rate variability and surface electromyography of trained cyclists at different cadences - Bruno Saraiva; Ester Silva; Rodrigo Polaquini Simões; Ana Paula Urdiales Garcia; Fabrício Augusto Menegon; Daniel Iwai Sakabe; Rodrigo Lício Ortolan; Luiz Eduardo Barreto Martins; Lucien Oliveira; Aparecida Maria Catai (Desafio Singular, 2016)
The heart rate variability (HRV) and surface electromyography (sEMG) are important tools in the evaluation of cardiac autonomic system and neuromuscular parameters, respectively. The aim of the study was to evaluate the behavior of HRV and sEMG of the vastus lateralis in two exercise protocols on a cycle ergometer at 60 and 80 rpm. Eight healthy men cyclists who have trained for at least two years were evaluated. Reduction was observed followed by stabilization of RMSSD and SDNN indices of HRV (p<0.05) along with increases in the amplitude of the sEMG signal (p<0.05) in both protocols. Significant correlations were observed between the responses of HRV and sEMG in the cadence of 60 rpm (RMSSD and sEMG: r = -0.42, p=0.03; SDNN and sEMG: r = -0.45, p=0.01) and 80 rpm (RMSSD and sEMG: r = -0.47, p=0.02; SDNN and sEMG: r = -0.49, p=0.01), yet no difference was observed for these variables between the two protocols. We concluded that the parasympathetic cardiac responses and sEMG are independent of cadences applied at the same power output.